Demokracja jako praktyka codziennego życia w przedszkolu. Z doświadczeń nauczycielek - Katarzyna Gawlicz (Problemy Wczesnej Edukacji)
The aim of this article is to explore the practical meaning of John Dewey’s claim that democracy has to be continuously recreated, by applying it to the preschool context. It takes its starting point in the notion of everyday democracy and, drawing on interviews with teachers who attempt to work democratically, points to the main challenges that arise in the course of this process. They include the need to constantly redefine the key concepts of freedom and equality, to confront and reconstruct the notions of the child and the teacher, and to avoid the risk of an instrumental use of seemingly democratic practice as classroom management technology.